2019
DOI: 10.1016/j.japh.2019.08.009
|View full text |Cite
|
Sign up to set email alerts
|

Attitudes and perceptions of naloxone dispensing among a sample of Massachusetts community pharmacy technicians

Abstract: Objectives: There is limited research on the attitudes of pharmacy technicians toward pharmacy naloxone provision, despite their widespread role in the pharmacy. We examined attitudes and perceptions of pharmacy technicians in the provision of naloxone in a sample of Massachusetts pharmacies. Design: Thirty-nine community retail pharmacies from 1 U.S. chain were purposely sampled in 13 municipalities across Massachusetts. Pharmacies were divided into high-risk municipalities (HRMs) versus low-risk municipaliti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
22
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 34 publications
0
22
0
Order By: Relevance
“…Contrary to bystanders’ perceptions about possible future discrimination, most pharmacists are supportive of naloxone, do not hold discriminatory attitudes towards naloxone patients, and are largely concerned that offering naloxone will offend or embarrass patients [ 31 ]. Additionally, pharmacy technicians are highly willing to provide naloxone and overdose education [ 35 ]. Universal offers of naloxone may be a useful intervention to close the gap between the perceptions of bystanders and pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…Contrary to bystanders’ perceptions about possible future discrimination, most pharmacists are supportive of naloxone, do not hold discriminatory attitudes towards naloxone patients, and are largely concerned that offering naloxone will offend or embarrass patients [ 31 ]. Additionally, pharmacy technicians are highly willing to provide naloxone and overdose education [ 35 ]. Universal offers of naloxone may be a useful intervention to close the gap between the perceptions of bystanders and pharmacists.…”
Section: Discussionmentioning
confidence: 99%
“…The large volume of NPS sales and variety of staff members selling and stocking NPS may explain the moderate correlation with administrative NPS sales data. Technicians and interns more commonly sell NPS than pharmacists and pharmacy managers; 29 self-reported data obtained from pharmacists may be less precise based on fewer interactions in some stores. Because pharmacy staff were surveyed by telephone, there is a potential for social desirability bias.…”
Section: Discussionmentioning
confidence: 99%
“…Certified pharmacy technicians have been trained to provide other health services such as immunizations, 32 and previous research has reported that technicians would benefit from overdose prevention training focused on increasing access to naloxone. 14 However, existing literature related to naloxone dispensing at pharmacies has primarily focused on the attitudes of pharmacists and their role in combating the opioid crisis. 33 CONSIDER New Mexico results demonstrated a statistically significant improvement in the intent of technicians to regularly introduce the potential need for naloxone to patients at risk of an opioid overdose following the intervention.…”
Section: Science and Practicementioning
confidence: 99%
“…12,13 Emerging research shows that pharmacy technicians are willing to identify patients who might benefit from having naloxone available and support dispensing. 14 However, stigma toward opioid-using patients is a substantial barrier. 15,16 Pharmacy technicians can benefit from training and professional development regarding opioid use disorder, implicit bias, and nonjudgmental approaches.…”
Section: Introductionmentioning
confidence: 99%